2021
DOI: 10.21070/perisai.v5i1.1317
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Sharia Banks as Nazhir Partners in the Management of CWLS Retail SWR001 Investment Products

Abstract: Islamic social finance, one of which waqf should have a position and role that can synergize to contribute economically, considering Indonesia has the largest Muslim population in the world. The issue that the potential waqf assets of 2000 trillion with about 51,155.57 ha of waqf land that exists today has not been a productive asset that serves as a source of income in developing the people's economy. While the potential of cash waqf that reaches Rp 180 trillion (BWI) but collected around 391 billion. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 6 publications
0
7
0
1
Order By: Relevance
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…This diagram summarizes the research approach used in research methodology related to CWLS in the scientific literature. It can be concluded that in the realm of research on CWLS, the dominant prevalence was found in the form of qualitative investigations in the form of literature studies with a percentage of 64.71% Afrianti, 2022;Anindhita et al, 2022;Armen et al, 2022;Cahyono et al, 2022;Hafandi et al, 2021;Indra et al, 2020;Istikomah et al, 2021;Lailatullailia et al, 2021;Maesarach et al, 2022;Mudriqoh, 2023;Mukti et al ., 2022;Nugroho et al, 2022;Puspitasari et al, 2022;Putri et al, 2020;Rahayu et al, 2020;Rahman et al, 2021;Maulina, 2022;Sa'idaturrohman , ;Sasongko et al, 2021;Siswantoro, ;Sulaeman et al, 2022;Tanjung & Agus, 2021 ;Ubaidilaah & Wahyu, 2021;Winarto et al, 2021; ANP (Afifah et al, 2022 ;Rabbani et al;Suratman et al, 2023) (Nurjamil, 2021), content analysis (Wati et al, 2022) and SLR Joseph, 2022).…”
Section: Cluster 4: Cwls Research Methodology (Additional)mentioning
confidence: 99%
“…Pada operasinya bank syariah tidak hanya berprinsip mencari keuntungan saja, melainkan memerhatikan aspek-aspek sosial di dalamnya. (Dian Lailatullailia et al, 2021) Bahkan secara hukum bank syariah diatur dalam peraturan BI Nomor 6/24/PBI/2004 tentang Bank Umum yang Melaksanakan Kegiatan Usaha Berdasarkan Prinsip Syariah. Pada pasal 36 dijelaskan bahwa Bank wajib menerapkan prinsip syariah dan prinsip kehati-hatian dalam melakukan kegiatan usahanya, yakni meliputi melakukan penghimpunan dana dari masyarakat dalam bentuk simpanan dan investasi, salah satunya yaitu tabungan (Wijaya, 2021).…”
Section: Bank Syariah Indonesia Tabungan Easy Wadiah Strategi Pemasaranunclassified
“…In addition, research conducted by Prananingtyas and Disemadi (2020) shows that the collection of cash waqf at KSPPS/USPPS has only reached IDR 33.7 billion. The data shows that there are still fundamental issues that need to be resolved regarding the potential and gaps in the realization of cash waqf collection in this most generous country (Lailatullailia et al, 2021;Zatadini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%